Construction of digital twin system for cold chain logistics stereo warehouse - Hu, Bin; Guo, Hui; Tao, Xiongjie; Zhang, Yingyi (IEEE access, 2023)
The current stereo warehouse in the cold chain logistics industry faces problems such as high product loss rate, severe temperature deviations, and low level of informatization. To ensure the food quality and safety of cold chain logistics warehouses, and achieve cost reduction and efficiency improvement, this study focuses on the operational scenarios of stereo warehouses in cold chain logistics, and designs a five-dimensional digital twin model with full mapping and multidimensional simulation. By integrating heterogeneous data from multiple sources, it achieves real-time visualization and monitoring of all elements in warehouses, and proposes a model optimization strategy that supports system-linked decision-making. This strategy intelligently adjusts the load and thermal distribution in the temperature-controlled zones of warehouses to maximize operational efficiency and reduce operating costs. Using this approach, a digital twin system for cold chain logistics warehouses was constructed. By comparing the warehouse operation data before and after optimization, the loss rate of fresh vegetables under the same storage conditions was reduced by 25-30%. This system achieves precise mapping and coordinated operation of real-time data from cold chain logistics warehouses and dynamic virtual models. The practical application of this solution is demonstrated in a cold-chain warehouse of a supply chain company in Guangdong, forming an integrated control model for cold chain logistics warehouses. This model provides a reference for the application of digital twin technology in the operation, scheduling, decision-making, and collaborative operations of cold chain logistics warehouses and offers new possibilities for establishing improved packaging for perishable products and ensuring cold chain food quality and safety.